Challenges in Using Modular Approach in Mathematics to Senior Students in Zambales Philippines - Kwajalynne C. Alegre; Teresita A. Falle (East Asian Journal of Multidisciplinary Research, 2023)
The study aimed to identify challenges faced by Grade 11 Senior High School students in using a modular approach for learning Mathematics in the San Felipe District, Division of Zambales, during the school year 2020–2021. A descriptive research design was employed, and data was collected through a questionnaire from 144 randomly selected student respondents. The findings revealed that the student respondents were typically female teenagers, with fathers working as farmers and mothers as housekeepers. The students rated the challenges of using the modular learning approach as "challenging" in terms of Subject Matter Content, Delivery and Retrieval, and Family Support. The researcher recommended implementing interventions to alleviate challenges among students, parents, teachers, and school administrators. Suggestions included promoting collaborative learning among neighbors, forming subject area expert committees to review module content, managing time effectively, ensuring clear and visual module materials, incorporating relevant activities, and conducting further studies to validate the findings.